Theoretical and Pedagogical Foundations of the Process Approach to ESL Composition - Jesús Alirio Bastidas (Asociación Colombiana de Profesores de Ingles, 2016)
In a recent article, Hamp-Lyons (1986) asserted that the process approach has had a "tremendous impact" on the teaching and the research of second language (L2) writing. Motivated by the previous assertion, this paper, first, attempts to identify some of the main theoretical and pedagogical features of this approach based on Zamel's (1983), Raimes' (1983), Horowitz' (1986), Liebman-Kleine's (1986), and Silva's (1990) articles. Then an analysis of some of its shortcomings is provided. This reaction paper has been facilitated by the influential framework of approach, design and procedure by Richards & Rodgers (1992) in order to analyze and evaluate a teaching method.